Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Bangun Ruang Sisi Datar Berdasarkan Kemampuan Berpikir Kritis - Stevania Sri Debbye Br Simbolon; Jesiska Anjelin Siagian; Cut Rania Andini (Supermat : Jurnal Pendidikan Matematika, 2025)
Mathematical critical thinking ability is an essential competence in 21st-century learning, as it enables students to understand, analyze, and solve problems logically and systematically. However, students’ mathematical critical thinking ability in the topic of solid figures with flat surfaces remains relatively low. Therefore, this study aims to describe the profile of students’ mathematical critical thinking ability and to analyze students’ errors in solving problems related to solid figures with flat surfaces based on critical thinking indicators. This study employed a descriptive qualitative approach involving 25 ninth-grade students at UPT SMP Negeri 10 Medan. The research instruments consisted of an essay test designed according to four indicators of mathematical critical thinking interpretation, analysis, evaluation, and inference and an interview guideline to explore the causes of students’ errors. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that students’ mathematical critical thinking ability predominantly falls into the low category, with 22 students classified as low, 3 students as moderate, and no students reaching the high category. The percentage of achievement for each indicator shows that interpretation reached 85.93%, analysis 81.64%, evaluation 75.39%, while inference was the lowest indicator at 18.75%. Interview findings reveal that students’ errors are mainly related to inaccuracies in identifying given and required information, failure to write appropriate formulas, incorrect problem-solving strategies, and the absence of final conclusions. These findings suggest that students’ mathematical critical thinking processes have not been carried out systematically from problem comprehension to conclusion drawing. Therefore, instructional strategies emphasizing structured and step-by-step critical thinking processes are recommended to enhance students’ mathematical critical thinking abilities.